Exploring Local Initiatives to Improve the Work Environment: A Qualitative Survey in Swedish Home Care Practice. Issue 3 (August 2021) - Rydenfält, Christofer; Persson, Roger; Arvidsson, Inger; Holgersson, Charlotte; Johansson, Gerd; Östlund, Britt; Persson, Johanna
Home care for the elderly constitutes a large and growing part of the social welfare system. Though, home care work is associated with a number of work environment-related challenges, including an increased risk for injuries, musculoskeletal disorders, high levels of sick leave and staff turnover, as well as stress and high workload, research is sparse. The present study explores local initiatives to improve the work environment initiated by the home care organizations themselves, and asks whether or not these initiatives affected gender equality. A qualitative web survey was sent to Swedish home care organizations, with open questions about change initiatives intended to have a positive effect on the work environment. There is an impressive amount of local work environment-related change initiatives going on. 80 categories of change initiatives were identified in answers from 178 units. However, these change initiatives were seldom evaluated or made accessible to stakeholders outside the organization. Main themes were concerned with work organization, digitalization, and planning, which largely follows trends in society (ie, digitalization, teamwork), rather than the actual needs identified by research (eg, musculoskeletal disorders). Despite apparent gender-related challenges, little of the work was associated with gender equality. The results indicates that there is a huge learning potential as the identified initiatives can serve as inspiration for others. However, to fully take advantage of these type of initiatives, more systematic evaluations are required.